Computation of the Rational Representation for Solutions of High-Dimensional Systems (Communications in Mathematical Research, 2021)
This paper deals with the representation of the solutions of a polynomialsystem, and concentrates on the high-dimensional case. Based on the rational univariate representation of zero-dimensional polynomial systems, we give a new descriptioncalled rational representation for the solutions of a high-dimensional polynomial system and propose an algorithm for computing it. By this way all the solutions of anyhigh-dimensional polynomial system can be represented by a set of so-called rational-representation sets.